EKSPERIMENTASI MODEL PEMBELAJARAN SURVEY, QUESTION, READ, RECITE, REVIEW (SQ3R) DAN SURVEY, QUESTION, READ, REFLECT, RECITE, REVIEW (SQ4R) DITINJAU DARI JENIS KELAMIN DAN GAYA BELAJAR - Wulandari, Septi; Budiyono, Budiyono; Iswahyudi, Gatut (Jurnal Pembelajaran Matematika, 2016)
Abstract:Â The aims of the research was to determine the effect of learning models on mathematics learning achievement viewed from gender and the student learning styles. The learning models compared were SQ3R, SQ4R, and direct instruction. This was a quasi experimental research using 3x2x3 factorial designs. The hypotheses testing used three ways ANOVA with unbalance cell. This research concludes that: (1) SQ4R learning provided better mathematics learning achievement than SQ3R and direct instruction, while direct instruction provided better mathematics learning achievement than SQ3R; (2) girls had better mathematics learning achievement than boys; (3) the students with visual, auditory, and kinesthetic learning style, there was no difference in mathematics learning achievement; (4a) boys taught with SQ4R had better mathematics learning achievement than SQ3R and direct instruction, boys taught with SQ3R had mathematics learning achievement as good as direct instruction; (4b) girls taught with SQ4R and direct instruction had better mathematics learning achievement than SQ3R. Girls taught with SQ4R had mathematics learning achievement as good as direct instruction; (5a) the students with visual learning style who were taught SQ4R had better mathematics learning achievement than SQ3R. the students with visual learning style who were taught SQ4R had mathematics learning achievement as good as direct instruction, while students with visual learning style who were taught SQ3R provided mathematics learning achievement as good as direct instruction; (5b) the students with auditory learning style who were taught SQ4R had better mathematics learning achievement than SQ3R and direct instruction. Students with auditory learning style who were taught SQ3R had mathematics learning achievement as good as direct instruction; (5c) the students with kinesthetic learning style who were taught SQ4R had better mathematics learning achievement than SQ3R. Students with kinesthetic learning style who were taught SQ3R had mathematics learning achievement as good as direct instruction. Students with kinesthetic learning style who were taught SQ4R had mathematics learning achievement as good as direct instruction; (6) in the model of learning SQ3R, SQ4R, and direct instruction, not only boys but also girls with visual learning style hadÂ mathematics learning achievement as good as they with auditory, and kinesthetic learning styles.Keywords: SQ3R, SQ4R, Gender, Learning Style, Mathematics Learning Achievement